Development of hydroxyapatite as a bone implant biomaterial for triggering osteogenesis - Pratama, Yusuf Alif; Dzikri Marhaeny, Honey; Deapsari, Fani; Budiatin, Aniek Setiya; Rahmadi, Mahardian; Miatmoko, Andang; Bakhtiar, M. Taher; Khotib, Junaidi (Thieme Medical and Scientific Publishers Pvt. Ltd., 2025)
Over the past decade, the occurrence of bone defects has seen a notable rise. In both developed and developing nations, their prevalence tends to increase in parallel with population density and levels of physical activity. Various therapeutic approaches have been implemented to address bone fractures, focusing on preventing infections, promoting faster healing, and restoring normal bone function. Among these, bone grafting—a surgical technique involving the use of biomaterials—remains a widely utilized method for bone replacement. This review aims to identify biomaterials that have biocompatibility with bone, osteoinductive, and osteoconductive properties so that they can trigger good osteogenesis. This review is based on a compilation of publications from various databases related to factors affecting the process of bone ossification. This study also evaluates the characteristics of hydroxyapatite biomate- rials that play a role in inducing osteogenesis. The phosphate/calcium ratio close to 1.67, porosity in the range of 40 to 60%, pore diameter of 200 to 900nm, and crystallinity of 40 to 60% will help the osteogenesis to perform well. The results of this study highlight the advantages of hydroxyapatite in terms of its osteoconductive, osteoinductive, and osteointegrative properties, which can trigger osteogenesis.